2011
DOI: 10.1590/s1983-14472011000300023
|View full text |Cite
|
Sign up to set email alerts
|

Triagem neonatal: o conhecimento materno em uma maternidade no interior do Paraná, Brasil

Abstract: This is a cross-sectional quantitative study quantitative held in the rooming area of a medium-sized hospital in the hinterlands of Paraná, Brazil. 40 mothers over 18 years participated in the study. The study aimed to examine what this population knows about the purpose and importance of completing the "Guthrie test" and also to characterize these mothers sociodemographically. The data were collected in May and June 2010 through a semi-structured questionnaire developed and implemented by the researchers them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
13

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 9 publications
2
4
0
13
Order By: Relevance
“…The lack of information may negatively affect the test performance, compromising the early diagnosis, the beginning of the treatment and its continuity. Brazilian research carried out along with the PNTNs identified mothers and relatives not aware about TP [16][17][18][19][20] . Health Education constitutes a set of knowledge and practices oriented towards disease prevention and health promotion 21,22 which can be implemented through Distant Learning (DL) 23 .…”
Section: Introductionmentioning
confidence: 99%
“…The lack of information may negatively affect the test performance, compromising the early diagnosis, the beginning of the treatment and its continuity. Brazilian research carried out along with the PNTNs identified mothers and relatives not aware about TP [16][17][18][19][20] . Health Education constitutes a set of knowledge and practices oriented towards disease prevention and health promotion 21,22 which can be implemented through Distant Learning (DL) 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Assim, a partir do relato das entrevistadas e de estudos que reforçaram a fragilidade das informações e do comprometimento profissional das profissionais que interagem com a população alvo do PNTN (5)(6)9) , é possível afirmar que o grau de ciência sobre a finalidade do exame, por parte das mães e familiares, resulta da forma como as orientações são passadas pelos profissionais da saúde, no caso, pela enfermeira, pois, para existir prevenção, é indispensável que as pessoas tenham uma adequada informação.…”
Section: Discussionunclassified
“…O exame de TN é uma medida preventiva que compete à enfermeira, que tem fundamental participação no processo de implementação do PNTN, esclarecer aos cuidadores sobre a importância e a finalidade do exame, do procedimento em si, bem como, da necessidade de buscar o resultado (5)(6) .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Deste modo, os estudos têm investigado o papel da enfermagem no TP, com enfoque no conhecimento desses profissionais e no procedimento de coleta deste exame (ACOSTA; STREFLING; GOMES, 2013;BENINCASA et al, 2009;STREFLING et al, 2014;PIMENTE et al, 2010). Essa fragilidade quanto à atuação da equipe de enfermagem em educação em saúde pode ter refletido diretamente no conhecimento superficial dos pais sobre esse exame (ABREU; BRAGUINI, 2011;SALLES;SANTOS, 2009;SANTOS et al, 2011 No ensino superior, o tema TP foi abordado principalmente em aulas expositivas (67,4%) de disciplinas ofertadas nos semestres finais do curso de graduação em enfermagem. As disciplinas referidas pelos acadêmicos que mais abordaram esse tema foram: Assistência integral à saúde da criança e adolescente (41,5%), Enfermagem em pediatria (35,6%) e Enfermagem na saúde da criança (33,3%).…”
Section: Introductionunclassified